Injectable Tissue-Engineered Soft Tissue for Tissue Augmentation - Rhee, Sung-Mi (J Korean Med Sci, 2014)
Soft tissue augmentation is a process of implanting tissues or materials to treat wrinkles or soft tissue defects in the body. Over the years, various materials have evolved to correct soft tissue defects, including a number of tissues and polymers. Autogenous dermis, autogenous fat, autogenous dermis-fat, allogenic dermis, synthetic implants, and fillers have been widely accepted for soft tissue augmentations. Tissue engineering technology has also been introduced and opened a new venue of opportunities in this field. In particular, a long-lasting filler consisting of hyaluronic acid filler and living human mesenchymal cells called "injectable tissue-engineered soft tissue" has been created and applied clinically, as this strategy has many advantages over conventional methods. Fibroblasts and adipose-derived stromal vascular fraction cells can be clinically used as injectable tissue-engineered soft tissue at present. In this review, information on the soft tissue augmentation method using the injectable tissue-engineered soft tissue is provided. GRAPHICAL ABSTRACT: [Image: see text]